2017
DOI: 10.1080/02786826.2016.1271938
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radical formation and soluble trace metal content in particulate matter from renewable diesel and ultra low sulfur diesel in at-sea operations of a research vessel

Abstract: Reactive oxygen species, including hydroxyl radicals generated by particles, play a role in both aerosol aging and PM2.5 mediated health effects. We assess the impacts of switching marine vessels from conventional diesel to renewable fuel on the ability of particles to generate hydroxyl radical when extracted in a simulated lung lining fluid or in water at pH 3.5, for samples of engine emissions from a research vessel when operating on ultra-low sulfur diesel (ULSD) and hydrogenation-derived renewable diesel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…For the PdB site, the contributions are a bit lower. Although only 2 sites presented an HFO factor, and similarly to previous studies (Hu et al, 2008;Kuang et al, 2017;Moldanová et al, 2013;Wang et al, 2020), it suggests that the PM originated from this source may significantly contribute to the total OP around harbor cities.…”
Section: Heavy Fuel Oilsupporting
confidence: 84%
“…For the PdB site, the contributions are a bit lower. Although only 2 sites presented an HFO factor, and similarly to previous studies (Hu et al, 2008;Kuang et al, 2017;Moldanová et al, 2013;Wang et al, 2020), it suggests that the PM originated from this source may significantly contribute to the total OP around harbor cities.…”
Section: Heavy Fuel Oilsupporting
confidence: 84%
“…The collection and analysis methods are described in more detail by Kuang et al . ( 32 ) and are described only briefly here. PM2.5 or PM4 was collected on 47-mm Teflon filters (Pall Inc.) in sets of five, plus matched field blanks at three urban locations in California: Claremont, an urban/receptor site in southern California, during summer when SOA peaks; Fresno, during winter when biomass burning aerosol makes a substantial contribution to particulate matter (PM), especially at night and in the morning; and West Los Angeles, a relatively clean urban site about 8 km from the Pacific Ocean.…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of H 2 O 2 , Fe(III) is known to undergo Reaction (1) (Neyens and Baeyens, 2003;Pignatello et al, 2006), resulting in the formation of Fe(II) and HO 2 (Pignatello et al, 2006;Rubio-Clemente et al, 2014), which degrades into superoxide, O − 2 , and H + (Reaction 2). Superoxide has the ability to oxidize organic compounds, particularly aromatic structures (Reaction 3) (Lair et al, 2008). The resulting structures of these oxidized compounds typically have two oxygen atoms, which could be arranged in various functional groups (Lair et al, 2008;Rubio-Clemente et al, 2014) as observed from the HPLC chromatograms.…”
Section: Iron-carbon Interactionsmentioning
confidence: 99%
“…Superoxide has the ability to oxidize organic compounds, particularly aromatic structures (Reaction 3) (Lair et al, 2008). The resulting structures of these oxidized compounds typically have two oxygen atoms, which could be arranged in various functional groups (Lair et al, 2008;Rubio-Clemente et al, 2014) as observed from the HPLC chromatograms. Oxidized single-ring aromatic structures have a strong affinity to iron and have the ability chelate iron into aqueous solution Hosseini and Madarshahian, 2009).…”
Section: Iron-carbon Interactionsmentioning
confidence: 99%